Legal Consequences of Child Marriage Judging from Law No. 35 of 2014 Concerning Child Protection - Amalia Aryani; Ayudya Puzhanurina; Faura Irsyadianty Waluyo; Ratu Bilqisy (IHSA Institute, 2022)
This study aims to analyze the legal consequences of child marriage in terms of law no. 35 of 2014 concerning child protection. The research method used is normative law, namely the library research method. The results of the analysis show that the legal consequences of underage marriages have an impact on their marital status; child's position; assets in marriage and children who receive a marriage pension. Efforts to prevent child marriage from occurring are by not asking parents for a marriage dispensation for any reason, unless it is really an emergency such as getting pregnant out of wedlock to save the child they are carrying. consequence, the opening of dispensation opportunities may worsen the condition of the quality of children's growth in Indonesia because they lose access to education and the opportunity to develop and understand responsibilities in marriage prior to marriage. child rights. In relation to underage marriages that can hinder child protection, it is necessary to improve the Child Protection Act in regulating the protection of children from underage marriages. Due to the threat that endangers the child's self and soul in the period of growth and development, special protection has the right to be given to the child.